Allosaurus the troublesome tooth - Veitch, Catherine; Brown, Steve (Essex, England Miles kelly, 2018)
Ava is an Allosaurus with a very sore tooth and it's making her feel grumpy. She doesn't want to play with her friends, but each of them want to try and help Ava get rid of her toothache - will any of their ideas work?
English stories
2
Keywords: Allosaurus -- Juvenile fiction; Dinosaurs -- Juvenile fiction